The observed variance of dʹ estimates compared across the 2-AFCR, Triangle, and Tetrad tasks. (September 2022) - Hautus, M.J.; van Hout, D.; Lee, H.-S.; Stocks, M.A.; Shepherd, D.
Highlights: Compared variance in d ′ for replicated performance across task type and difficulty. Employed 2-AFC with Reminder (2-AFCR), Triangle, and Tetrad tasks. On a difficult task, 2-AFCR had lower variance than the Triangle or Tetrad tasks. On a mid-difficulty task, 2-AFCR had lower variance than the Triangle. No differences in the variance of d ′ were observed for the easy task. Abstract: Sensory scientists are commonly tasked with determining whether consumers will be able to detect changes in product formulations or ingredients. To this end, sensory panels are formed and discrimination tasks employed, of which numerous types exist. This research compares the performance of three discrimination tasks: the traditional triangle task and two more modern tasks, the two-alternative forced-choice with reminder (2-AFCR) and Tetrad tasks. Comparisons were in terms of observed performance without reliance on the binomial assumption implicit in most contemporary methods of analysis. Seven judges tasted aqueous solutions containing orange essence and were asked to identify the sample containing the greatest amount of essence. Orange essence concentrations were tailored to each individual judge during preliminary testing, and three concentrations of orange essence, greater than the fixed concentration of the reference sample were determined for each judge. Across judges, these were referred to as the easy, medium, and hard levels. To compare discriminability across the three tasks the sensitivity index dʹ was calculated. For the 2-AFCR task, this first required the decision strategy used by the judges to be determined. In general, the judges most likely used the β/τ strategy in 2-AFCR. Across the three tasks, average dʹ values for the same judges, discriminating between the same stimuli, were not significantly different. However, the 2-AFCR task had significantly lower sample variances of d ′ than the Triangle or Tetrad tasks at low levels of d ′ (the hard level), and than the Triangle task at the medium level of difficulty. No differences were observed at the easy level.